Flame-retardant cable lubricant suitable for enameled round aluminum wire and preparation method and application thereof

By using polyether modified silicone oil, phosphorus-containing monomer, nitrogen-containing monomer and nano-enhancing agent in enameled wire lubricant, a cross-linking network is formed, which solves the problem of insufficient thermal stability and adhesion of lubricant in high-temperature environments. It significantly improves flame retardant performance and oxidation resistance, and meets the use requirements in high-temperature and high-speed environments.

CN119144383BActive Publication Date: 2025-02-18SHANDONG HUILONG ELECTRICAL MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411626804.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

Existing enameled wire lubricating oils show insufficient thermal stability and adhesion in high temperature environments, and insufficient flame retardant performance, which affects the service life of the wire and poses safety hazards.

Method used

Polyether modified silicone oil is used as the base oil, combining phosphorus-containing monomers and nitrogen-containing monomers, and cross-linking networks are formed by initiators and cross-linking agents. The addition of nano-enhancing agents such as organically modified montmorillonite nanosheets can enhance lubricating oil. flame retardant, thermal stability, antioxidant and adhesion properties.

Benefits of technology

It significantly improves the flame retardant performance, thermal stability, oxidation resistance and adhesion of lubricating oil, meets the requirements of use in high temperature and high speed environments, and ensures the long-term lubrication effect and safety of enameled round aluminum wire.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of lubricating oils, and discloses a flame-retardant wiring lubricant suitable for enameled round aluminum wires, a preparation method thereof, and an application thereof, wherein the lubricant comprises the following components by mass percentage: 40-60 wt% of base oil, 10-30 wt% of phosphorus-containing monomers, 10-20 wt% of nitrogen-containing monomers, 1-5 wt% of initiators, and 1-5 wt% of cross-linking agents; preferably, 3-8 wt% of nano-enhancers, 0.3-1 wt% of antioxidants, and 0.1-0.5 wt% of ultraviolet light stabilizers are also included. The base oil is a polyether-modified silicone oil, the phosphorus-containing monomer is a phosphate functional group copolymer monomer, the nitrogen-containing monomer is a polar monomer having a nitrogen heterocyclic structure, and the nano-enhancer is a montmorillonite nanosheet whose surface is modified by an organic functional group. The lubricant of the present invention has excellent flame retardancy, thermal stability, and adhesion, and is particularly suitable for use of enameled round aluminum wires in high temperature and high-speed environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lubricating oils, in particular to a flame-retardant wiring lubricating oil suitable for enameled round aluminum wires and a preparation method and application thereof. Background Art

[0002] Enameled round aluminum wire is widely used in motors, transformers and electronic components. Its surface needs to be coated with lubricant to improve lubricity, wear resistance and stability during winding. However, traditional enameled wire lubricants often show poor thermal stability and adhesion in high temperature environments, making it difficult to meet the requirements of modern industry for high temperature and high speed operations. Especially in high temperature or spark environments, the lubricant's flame retardant properties are insufficient, which not only affects the service life of the wire, but also poses a safety hazard.

[0003] Existing lubricant formulas usually rely on mineral oil or simple silicone oil as the base oil. Although they have a certain lubricating effect, their heat resistance and flame retardancy are obviously insufficient. At the same time, traditional lubricants lack effective flame retardant ingredients, are easy to burn when exposed to high temperatures, and are difficult to form a protective layer, thus failing to effectively isolate oxygen and heat sources. In addition, ordinary antioxidants and UV stabilizers often fail to provide adequate protection under extreme conditions, causing the lubricant to easily oxidize and degrade under high temperatures or UV light, accelerating its aging and failure. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a flame retardant wiring lubricant suitable for enameled round aluminum wire and a preparation method and application thereof, which solves the problems of insufficient flame retardancy, thermal stability, oxidation resistance and adhesion of existing enameled wire lubricants under high temperature and high speed environments.

[0005] To achieve the above object, the present invention is implemented by the following technical scheme: a flame retardant wiring lubricant suitable for enameled round aluminum wire, comprising the following components by mass percentage:

[0006] Base oil 40-60 wt%;

[0007] Phosphorus-containing monomer 10-30 wt%;

[0008] Nitrogen-containing monomer 10-20 wt%;

[0009] Initiator 1-5 wt%;

[0010] Crosslinking agent 1-5 wt%.

[0011] Preferably, the base oil is a polyether-modified silicone oil formed by alternating copolymerization of polyether groups and siloxane segments, and its molecular structure contains multiple ether bonds and siloxane bonds;

[0012] The high bond energy of silicon-oxygen bonds (Si-O) endows the base oil with excellent high temperature resistance, making it stable and not easy to decompose under extreme temperature conditions, thus ensuring that the lubricant maintains good lubrication during high temperature winding;

[0013] The ether bond in the polyether group has good flexibility and polarity, and can form excellent compatibility with other components and the surface of the enameled wire, improve the fluidity and adhesion of the lubricant, and is particularly suitable for high-speed operation environments;

[0014] Through the synergistic effect of silicone segments and polyether groups, the base oil not only has extremely low surface tension and friction coefficient, but also can effectively improve the oxidation resistance and durability of the lubricant, thereby enhancing the overall lubrication effect and material stability.

[0015] Preferably, the phosphorus-containing monomer is a comonomer having a phosphate functional group, the structure of which contains at least one phosphorus-oxygen bond and can form a covalent bond with the base oil segment during the polymerization process;

[0016] Phosphate functional groups are pyrolyzed at high temperatures to generate phosphoric acid substances, which can quickly form a dense carbonized layer on the surface of the material, effectively isolating oxygen and heat sources and preventing the spread of flames;

[0017] The phosphorus-containing monomer forms a covalent bond with the base oil segment through its phosphorus-oxygen bond during the polymerization process, and is firmly embedded in the molecular skeleton of the lubricating oil, thereby enhancing the stability and heat resistance of the overall network structure.

[0018] Preferably, the nitrogen-containing monomer is a polar monomer having a nitrogen heterocyclic structure, and its molecular structure contains a pyrrolidone group or a similar nitrogen-containing group, which can form a copolymer with the base oil and the phosphorus-containing monomer in the polymerization reaction;

[0019] The strong polarity of nitrogen-containing groups such as pyrrolidone groups enables them to have excellent surface adhesion in lubricating oils, which can effectively enhance the chemical bonding between lubricating oils and the surface of enameled wires and improve the stability of the lubricating layer;

[0020] The nitrogen heterocyclic structure releases inert gas at high temperature, which synergizes with the carbonization effect of phosphate ester to enhance the flame retardant properties of the lubricant.

[0021] Through the above technical solution, the carbonization effect of phosphorus-containing monomers and the gas phase flame retardant effect of nitrogen-containing monomers form a complementary mechanism. The carbonized layer generated by phosphate ester can effectively isolate the heat source, while nitrogen dilutes oxygen to further inhibit combustion. The combination of the two significantly improves the flame retardant efficiency.

[0022] The excellent high temperature resistance of the base oil is chemically combined with phosphorus- and nitrogen-containing monomers to make the entire lubricant system more stable at high temperatures, prevent the rapid decomposition of the lubricant, and ensure long-term lubrication effect.

[0023] The polar groups of the nitrogen-containing monomers work synergistically with the silicon-oxygen segments of the base oil, so that the lubricant not only has excellent adhesion on the surface of the enameled wire, but also maintains low friction and high temperature resistant lubrication properties, making it suitable for high-speed operation environments.

[0024] In general, the lubricant of the present invention combines multiple functions such as physical flame retardancy, gas phase flame retardancy, thermal stability and lubrication performance to form a synergistic flame retardant lubricant system. This design not only performs well in flame retardancy and heat resistance, but also provides stable lubrication and adhesion, meeting the use requirements of enameled round aluminum wire in high temperature and high speed environments.

[0025] Preferably, the lubricating oil further comprises 3-8wt% of a nano-enhancer accounting for the total mass thereof, wherein the nano-enhancer is a montmorillonite nanosheet whose surface is modified with an organic functional group;

[0026] After montmorillonite nanosheets are modified with organic functional groups, their layered structure can be evenly dispersed in the lubricating oil, forming an effective physical barrier to prevent the diffusion of heat and gas, thereby enhancing the thermal shielding effect of the lubricating oil and further enhancing its flame retardant properties.

[0027] Nano-montmorillonite can significantly improve the structural strength and thermal deformation resistance of lubricating oil by forming a good interface bond with base oil and other components, making it more stable and durable in high temperature and high speed environments.

[0028] The high specific surface area and unique nano-scale size of nano-montmorillonite give it excellent dispersibility and reinforcement effects, which can significantly improve the overall performance of lubricants at a low addition amount.

[0029] Preferably, the lubricating oil further comprises:

[0030] Antioxidants, accounting for 0.3-1wt% of the total mass;

[0031] Antioxidants can capture free radicals generated by lubricating oil in high temperature environments, prevent oil oxidation and degradation, and extend the service life of lubricating oil. By adding antioxidants, the chemical stability of lubricating oil at high temperatures is enhanced, effectively avoiding performance degradation caused by oxidation.

[0032] UV stabilizer, accounting for 0.1-0.5wt% of the total mass;

[0033] UV stabilizers can absorb and dissipate ultraviolet rays, prevent photo-oxidative degradation of lubricating oils in light environments, and reduce oil aging and performance deterioration caused by ultraviolet rays. They are especially suitable for applications that may be exposed to outdoor or strong light environments.

[0034] The present invention also provides a method for preparing the flame-retardant wiring lubricant suitable for enameled round aluminum wire, comprising the following steps:

[0035] S1. Pretreatment of base oil

[0036] By heating the base oil to 40-60°C and degassing it under vacuum conditions for 10-30 minutes, the dissolved gas in the base oil can be effectively removed to avoid the formation of bubbles in the subsequent polymerization reaction, thereby ensuring the uniformity of the reaction and the stability of the product.

[0037] S2. Introduction of phosphorus-containing monomers

[0038] When adding phosphorus-containing monomers to the base oil, the stirring speed is controlled at 100-200 rpm and the stirring is carried out for 10-30 minutes to ensure that the phosphorus-containing monomers are fully mixed with the base oil without introducing too many bubbles, thereby ensuring the uniform distribution of the phosphorus-containing monomers in subsequent reactions and enhancing the flame retardant effect.

[0039] S3. Slow addition of nitrogen-containing monomers

[0040] Slowly add the nitrogen-containing monomer to the base oil, keeping the stirring speed at 100-200rpm to ensure full mixing. The slow addition process ensures the gradual and uniform dispersion of the nitrogen-containing monomer and avoids excessive reaction. The nitrogen-containing organic group can not only improve the adhesion of the lubricant in the subsequent reaction.

[0041] S4. Initiation of polymerization and cross-linking

[0042] Add initiator and crosslinker at 70-110℃ and stir for 2-5 hours to initiate polymerization of phosphorus-containing monomers and nitrogen-containing monomers with base oil. The initiator can generate free radicals to start the polymerization reaction of phosphorus-containing and nitrogen-containing monomers with base oil to form a crosslinked polymer network. Through the crosslinker, the molecular segments in the system form a more compact three-dimensional structure, which enhances the mechanical properties and high temperature resistance of the lubricant, allowing the lubricant to maintain good adhesion and lubrication effect under extreme conditions.

[0043] S5. Cooling and further degassing

[0044] Cool the reaction system to room temperature, continue stirring for 30-60 minutes, and degas for 10-20 minutes. The cooling process stabilizes the reaction system, while continued stirring promotes the complete reaction and ensures a uniform system. Degassing again ensures that there is no residual gas in the system, further improving the uniformity and stability of the lubricant.

[0045] S6. Viscosity adjustment

[0046] By adding base oil, the viscosity is adjusted to 150-200 cSt. Viscosity adjustment ensures that the fluidity and working performance of the lubricant are suitable for the high-speed winding process of enameled round aluminum wire. By precisely controlling the viscosity, the lubricant can provide sufficient lubrication under high temperature and high friction environment, while ensuring good adhesion and wear resistance.

[0047] Preferably, before the step S4, the method further comprises: ultrasonically dispersing the nano additive and a small amount of base oil for 20-40 minutes, then adding the nano additive to the base oil and stirring evenly;

[0048] Through ultrasonic treatment, the nano-additives can be evenly dispersed in the base oil to avoid agglomeration. This process ensures that the nano-sheets are fully dispersed, thus forming an effective physical barrier in the lubricant system, further enhancing the flame retardant properties and thermal stability of the lubricant.

[0049] Preferably, before the step S6, the method further comprises: adding an antioxidant and an ultraviolet light stabilizer when the temperature of the reaction system is 30-50° C., and stirring evenly;

[0050] Adding antioxidants at lower temperatures can capture and neutralize the free radicals generated during the reaction, preventing the degradation of the lubricant due to heat or oxidation, thereby extending the life and stability of the lubricant.

[0051] Through the above technical solutions, effective polymerization and cross-linking of phosphorus-containing and nitrogen-containing monomers and base oils are achieved, ensuring that the lubricant has excellent flame retardant, adhesion and lubrication properties. Through the pretreatment of base oil, dispersion of monomers, polymerization reaction and viscosity adjustment, the synergistic effect of each component is maximized, significantly improving the stability and performance of the lubricant.

[0052] The present invention also provides an application method of the flame-retardant wiring lubricant suitable for enameled round aluminum wire, comprising the following steps: evenly coating the lubricant on the surface of the enameled wire to ensure that the lubricant is fully covered.

[0053] The present invention provides a flame retardant wiring lubricant suitable for enameled round aluminum wires and a preparation method and application thereof. It has the following beneficial effects:

[0054] The present invention forms a carbonized layer and releases inert gas at high temperature through the synergistic effect of phosphorus-containing monomers and nitrogen-containing monomers, which respectively play the role of isolating heat sources and diluting oxygen, thereby significantly improving the flame retardant properties of lubricating oil. This design effectively inhibits the combustion process and ensures the safety of lubricating oil under high temperature conditions;

[0055] The present invention improves the thermal stability of lubricating oil by using polyether-modified silicone oil and organically modified montmorillonite nano-enhancer. The silicon-oxygen bond structure is resistant to high temperatures and is not easy to decompose. The nano-enhancer forms a physical barrier at high temperatures to block heat conduction and delay the thermal decomposition of the lubricating oil, ensuring that it remains stable in extreme temperature environments.

[0056] The present invention provides low friction and good lubrication performance through polyether-modified silicone oil, and the polar groups of nitrogen-containing monomers enhance the adhesion of the lubricant oil on the metal surface, thereby preventing the lubricant oil from falling off. In a high-temperature and high-speed environment, the lubricant oil can maintain stable adhesion and low friction characteristics for a long time, thereby improving the working efficiency and service life of the equipment;

[0057] The invention significantly improves the structural strength and mechanical properties of the lubricating oil by forming a three-dimensional cross-linked network through the initiator and the trifunctional cross-linking agent. This structural design not only ensures that the lubricating oil is not easy to soften or lose at high temperatures, but also has higher durability and stability under mechanical stress. DETAILED DESCRIPTION

[0058] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0059] The present invention provides a flame retardant wiring lubricant suitable for enameled round aluminum wires. By reasonably proportioning base oil, phosphorus-containing monomers, nitrogen-containing monomers, initiators, crosslinking agents and auxiliary components, a lubricant with excellent flame retardancy, thermal stability, oxidation resistance and adhesion is constructed. The following is a specific description of each component:

[0060] Base oil (40-60 wt%)

[0061] The base oil is the main component of the lubricating oil of the present invention, and preferably a polyether-modified silicone oil is used, which is formed by alternating copolymerization of polyether groups and siloxane segments, and contains multiple ether bonds and siloxane bonds in the molecular structure. The polyether group provides good lubricity and fluidity, ensuring that the lubricating oil maintains a stable friction coefficient under high temperature conditions; the siloxane bond gives the base oil excellent high temperature resistance and thermal stability, and is suitable for use under high speed and high temperature conditions. In addition, the low surface tension of the polyether-modified silicone oil makes it have better lubrication effect and durability on the metal surface.

[0062] Phosphorus-containing monomers (10-30 wt%)

[0063] The phosphorus-containing monomer is a comonomer containing a phosphate functional group, and its structure contains at least one phosphorus-oxygen bond. The phosphate functional group can decompose to generate phosphoric acid compounds at high temperatures, forming a dense carbonized layer during the combustion process, which plays an effective flame retardant role; in addition, the phosphorus-oxygen bond can form a covalent bond with the base oil segment during the polymerization process, enhancing the network structure stability of the lubricant. The addition of this phosphorus-containing monomer greatly improves the flame retardant properties of the lubricant, making it have strong fire resistance under high temperature conditions.

[0064] Nitrogen-containing monomers (10-20 wt%)

[0065] The nitrogen-containing monomer is a polar monomer with a nitrogen-containing heterocyclic structure, preferably containing a pyrrolidone group or a similar nitrogen-containing organic group. The pyrrolidone group has a strong polarity and can produce strong adhesion to the surface of the enameled wire, thereby improving the adhesion of the lubricant. The nitrogen-containing monomer decomposes at high temperatures to produce inert nitrogen, which further dilutes the oxygen in the combustion zone, inhibits the occurrence of combustion, and synergizes with the phosphorus-containing monomer to play a flame retardant role. In addition, the nitrogen-containing monomer forms a copolymer with the base oil and the phosphorus-containing monomer during the polymerization process, further improving the network strength and stability of the lubricant.

[0066] Initiator (1-5 wt%)

[0067] The initiator is tert-butyl peroxide (TBP) or other free radical initiators with thermal stability. The initiator decomposes under high temperature conditions to produce free radicals, which start the copolymerization of phosphorus-containing monomers and nitrogen-containing monomers to form a uniform cross-linked network structure. The high thermal stability of TBP ensures the stable release of the initiator during the reaction, allowing the copolymerization reaction to proceed at a stable temperature to form an efficient cross-linked network, thereby improving the high temperature resistance and structural strength of the lubricant.

[0068] Crosslinking agent (1-5 wt%)

[0069] The crosslinking agent is trimethylolpropane triacrylate (TMPTA) or other trifunctional crosslinking agents. TMPTA contains trifunctional groups and can crosslink with the functional groups of phosphorus-containing and nitrogen-containing monomers to form a dense three-dimensional network structure, further improving the mechanical strength and high temperature resistance of the lubricant. The crosslinking agent introduces more crosslinking points in the polymerization reaction, making the lubricant system more stable and able to maintain excellent performance under high temperature and high load conditions.

[0070] Nano-enhancement agent (3-8 wt%)

[0071] The preferred nano-enhancer is a montmorillonite nanosheet modified with an organic functional group. After the surface is organically modified, the nano-enhancer can form a good dispersion state with the base material of the lubricant. The layered structure of montmorillonite can provide a physical barrier at high temperatures, delaying the diffusion of heat and oxygen, thereby significantly improving the flame retardancy and thermal stability of the lubricant. The addition of the nano-enhancer also improves the mechanical properties of the lubricant, making it more durable in high temperature and high speed environments.

[0072] Antioxidant (0.3-1 wt%)

[0073] The antioxidant is a vitamin E derivative (such as tocopherol acetate), whose chemical structure has excellent antioxidant properties and can capture free radicals generated under high temperature conditions to prevent the lubricant from being degraded due to oxidation, thereby extending the service life of the lubricant. The addition of antioxidants ensures the chemical stability of the lubricant in long-term use, making it suitable for use in harsh environments.

[0074] UV stabilizer (0.1-0.5 wt%)

[0075] The UV stabilizer is 2-hydroxy-4-methoxybenzophenone (BP-3) or other compounds with the ability to absorb ultraviolet light. The addition of UV stabilizers protects the lubricating oil from UV degradation when exposed to light, slows down the aging phenomenon caused by photo-oxidation, and maintains the stability of the lubricating oil's performance, which is especially suitable for applications that require long-term outdoor use.

[0076] Preferably, the mixing and reaction conditions of the components are achieved by the following steps:

[0077] S1: Add polyether modified silicone oil as base oil into the reactor, heat to 40-60℃, and degas for 10-30 minutes under vacuum conditions to remove gas and trace impurities in the oil.

[0078] S2: Add phosphorus-containing monomer and control the stirring speed to 100-200 rpm for 10-30 minutes to fully mix it with the base oil.

[0079] S3: Slowly add the nitrogen-containing monomer, keeping the stirring speed at 100-200 rpm to ensure that the nitrogen-containing monomer is evenly dispersed with other ingredients.

[0080] S4: Mix the nano-enhancer with a small amount of base oil and treat it in an ultrasonic dispersion device for 20-40 minutes, then add it into the reactor and stir until it is uniform.

[0081] S5: Raise the temperature of the reaction system to 70-110°C, add initiator and cross-linking agent, and keep stirring for 2-5 hours to allow the system to fully undergo cross-linking reaction to form a stable polymerization network.

[0082] S6: After the reaction is completed, the system is cooled to room temperature, and stirring is continued for 30-60 minutes to ensure that the system is uniform, and degassing is performed for 10-20 minutes.

[0083] S7: When the temperature drops to 30-50℃, add antioxidant and UV stabilizer and stir evenly. Finally, adjust the viscosity to 150-200 cSt by adding base oil to meet the application requirements of lubricating oil.

[0084] The lubricating oil preparation method of the present invention enables it to have excellent flame retardancy, thermal stability, oxidation resistance and adhesion, and is particularly suitable for use in scenarios such as wires and cables in high-temperature and high-speed environments.

[0085] In order to better understand the present invention, the specific implementation methods of the present invention are described in detail below in conjunction with specific examples.

[0086] Embodiment 1, formula composition is as follows:

[0087] Base oil: 50wt%

[0088] Phosphorus-containing monomer: 20wt%

[0089] Nitrogen-containing monomer: 15wt%

[0090] Initiator: 3wt%

[0091] Crosslinking agent: 3wt%

[0092] Nano-enhancement agent: 5wt%

[0093] The preparation steps are as follows:

[0094] S1: Add polyether-modified silicone oil as base oil into a reactor and heat to 50°C, and degas under vacuum for 20 minutes;

[0095] S2: adding phosphorus-containing monomers with phosphate functional groups into the base oil, controlling the stirring speed to 150 rpm, and stirring for 15 minutes;

[0096] S3: slowly add the nitrogen-containing monomer of the pyrrolidone group, maintaining the stirring speed at 150 rpm, until it is evenly dispersed;

[0097] S4: Mix the nano-enhancer (montmorillonite nanosheets modified with organic functional groups) with a small amount of base oil, disperse it in an ultrasonic disperser for 30 minutes, add it into the reactor, and stir it evenly;

[0098] S5: Raise the temperature to 90°C, add initiator and crosslinker, and keep stirring for 3 hours to complete the polymerization reaction;

[0099] S6: Cool the reaction system to room temperature, continue stirring for 45 minutes and degas for 15 minutes;

[0100] S7: Add base oil to adjust the viscosity to 180 cSt.

[0101] Embodiment 2, formula composition is as follows:

[0102] Base oil: 45wt%

[0103] Phosphorus-containing monomer: 25wt%

[0104] Nitrogen-containing monomer: 10wt%

[0105] Initiator: 4wt%

[0106] Crosslinking agent: 4wt%

[0107] Antioxidant: 0.5wt%

[0108] UV stabilizer: 0.3wt%

[0109] The preparation steps are as follows:

[0110] S1: Heat the base oil to 55 °C and degas under vacuum for 20 minutes;

[0111] S2: Add phosphorus-containing monomer, control the stirring speed at 200 rpm, and stir for 20 minutes;

[0112] S3: slowly add nitrogen-containing monomer, control the stirring speed at 150 rpm, and stir until uniform;

[0113] S4: Raise the temperature to 95°C, add initiator and crosslinker, and keep stirring for 4 hours;

[0114] S5: Cool down to 40°C, add antioxidant and UV stabilizer, and stir for 30 minutes;

[0115] S6: Cool the system to room temperature, continue stirring for 60 minutes, and degas for 10 minutes;

[0116] S7: Add base oil to adjust the viscosity to 160 cSt.

[0117] Embodiment 3, formula composition is as follows:

[0118] Base oil: 45wt%

[0119] Phosphorus-containing monomer: 25wt%

[0120] Nitrogen-containing monomer: 10wt%

[0121] Initiator: 4wt%

[0122] Crosslinking agent: 4wt%

[0123] Antioxidant: 0.5wt%

[0124] UV stabilizer: 0.3wt%

[0125] The preparation steps are as follows:

[0126] S1: Heat the base oil to 55 °C and degas under vacuum for 20 minutes;

[0127] S2: Add phosphorus-containing monomer, control the stirring speed at 200 rpm, and stir for 20 minutes;

[0128] S3: slowly add nitrogen-containing monomer, control the stirring speed at 150 rpm, and stir until uniform;

[0129] S4: Raise the temperature to 95°C, add initiator and crosslinker, and keep stirring for 4 hours;

[0130] S5: Cool down to 40°C, add antioxidant and UV stabilizer, and stir for 30 minutes;

[0131] S6: Cool the system to room temperature, continue stirring for 60 minutes, and degas for 10 minutes;

[0132] S7: Add base oil to adjust the viscosity to 160 cSt.

[0133] Embodiment 4, formula composition is as follows:

[0134] Base oil: 60wt%

[0135] Phosphorus-containing monomer: 10wt%

[0136] Nitrogen-containing monomer: 20wt%

[0137] Initiator: 1wt%

[0138] Crosslinking agent: 4wt%

[0139] Nano-enhancement agent: 3wt%

[0140] Antioxidant: 0.4wt%

[0141] UV stabilizer: 0.1wt%

[0142] The preparation steps are as follows:

[0143] S1: Heat the base oil to 50°C and degas for 10 minutes;

[0144] S2: Add the phosphorus-containing monomer to the base oil, stirring at 100 rpm for 15 minutes;

[0145] S3: Add nitrogen-containing monomer, control the stirring speed at 100 rpm, and stir evenly;

[0146] S4: The nano-enhancer was ultrasonically dispersed in a small amount of base oil for 40 minutes and then added and stirred until uniform;

[0147] S5: Raise the temperature to 110°C, add initiator and crosslinker, and stir for 5 hours;

[0148] S6: Cool down to 40°C, add antioxidant and UV stabilizer, and stir for 35 minutes;

[0149] S7: Adjust the viscosity to 150 cSt.

[0150] Embodiment 5, formula composition is as follows:

[0151] Base oil: 48wt%

[0152] Phosphorus-containing monomer: 28wt%

[0153] Nitrogen-containing monomer: 12wt%

[0154] Initiator: 3wt%

[0155] Crosslinking agent: 3wt%

[0156] Nano-enhancement agent: 5wt%

[0157] Antioxidant: 0.5wt%

[0158] UV stabilizer: 0.2wt%

[0159] The preparation steps are as follows:

[0160] S1: Heat the base oil to 50°C and vacuum degas for 15 minutes;

[0161] S2: Add phosphorus-containing monomer, control the stirring speed to 150 rpm, and stir for 10 minutes;

[0162] S3: gradually add nitrogen-containing monomer and stir until uniform;

[0163] S4: Mix the nanoenhancer with a small amount of base oil, treat it in an ultrasonic disperser for 30 minutes, then add it and stir it evenly;

[0164] S5: Raise the temperature to 90°C, add initiator and crosslinker, and stir for 3 hours;

[0165] S6: When the temperature drops to 35°C, add antioxidant and UV stabilizer and stir for 40 minutes;

[0166] S7: Cool to room temperature, continue stirring for 30 minutes and degas, then adjust the viscosity to 200 cSt.

[0167] Performance Test:

[0168] Purpose: To evaluate the actual performance of the flame-retardant cable lubricants of the five embodiments above on enameled round aluminum wires.

[0169] Test items include flame retardancy, viscosity, thermal stability, antioxidant properties, UV stability, adhesion and friction coefficient.

[0170] 1. Flame retardancy test

[0171] Purpose: To determine the flame retardant properties of lubricating oil at high temperatures;

[0172] step:

[0173] Apply lubricating oil to the enameled wire and dry it;

[0174] Use a flame retardant tester to heat the sample to 450°C, and observe and record the formation of the carbonized layer and the burning time;

[0175] Record the flame retardant time (seconds) and the thickness of the charred layer (micrometers).

[0176] 2. Viscosity test

[0177] Purpose: To measure the dynamic viscosity of lubricating oil at different temperatures;

[0178] step:

[0179] The lubricating oil of each example was sampled and its viscosity (unit: cSt) was measured at 25°C, 50°C and 100°C using a viscometer;

[0180] Record the viscosity value of each sample at different temperatures.

[0181] 3. Thermal stability test

[0182] Objective: To evaluate the thermal decomposition characteristics of lubricating oil in high temperature environment;

[0183] step:

[0184] Take 10g of lubricating oil sample and place it in a thermogravimetric analyzer (TGA);

[0185] Heating from room temperature to 600°C, heating rate 10°C / min;

[0186] The decomposition temperature of the lubricating oil of each example was recorded (the temperature was recorded when the mass loss was 5%).

[0187] 4. Antioxidant performance test

[0188] Purpose: To test the oxidation stability of lubricating oil in oxygen environment;

[0189] step:

[0190] The lubricating oil sample was heated to 150°C in an oxygen environment for 8 hours;

[0191] Fourier transform infrared spectroscopy (FTIR) was used to analyze the oxidation changes of the oil samples;

[0192] The oxidation induction time (OIT, unit: minutes) was recorded.

[0193] 5. UV light stability test

[0194] Purpose: To evaluate the stability of lubricating oil under UV light;

[0195] step:

[0196] The lubricating oil sample was placed in a UV aging box (wavelength 254 nm) and irradiated for 24 hours;

[0197] The absorbance change was detected using a UV spectrophotometer;

[0198] Record the decay rate (%) of UV absorbance.

[0199] 6. Adhesion test

[0200] Purpose: To detect the adhesion of lubricating oil on the surface of enameled wire;

[0201] step:

[0202] Apply lubricating oil on the enameled wire and let it dry;

[0203] Use the cross-hatch test method to draw a grid with a spacing of 1 mm on the coating surface;

[0204] Use tape to pull on the mesh surface and observe the peeling of the coating;

[0205] The attachment grade was recorded (0-5, with 0 being the best).

[0206] 7. Friction coefficient test

[0207] Purpose: To test the friction coefficient of lubricating oil to evaluate its lubricating effect;

[0208] step:

[0209] The test was carried out on a friction tester, with the sliding speed set to 10 mm / s and a load of 5 N applied;

[0210] Record the coefficient of friction (unitless) for the different samples.

[0211] The performance test results are shown in the following table:

[0212] .

[0213] According to the results of the data in the above table, the following is a summary analysis of the flame retardancy, thermal stability, oxidation resistance, UV stability, adhesion and lubricity of the embodiments of the present invention.

[0214] Significantly improved flame retardant performance

[0215] All examples showed good flame retardant effects in the flame retardant test, with flame retardant time in the range of 60-70 seconds and carbonized layer thickness maintained at 18-24 microns. This is due to the synergistic effect of phosphorus-containing monomers and nitrogen-containing monomers, the former forming a carbonized layer at high temperature and the latter releasing inert gas to further inhibit the spread of combustion. In particular, Example 4, under the optimal ratio of phosphorus-containing and nitrogen-containing components, both flame retardant time and carbonized layer thickness reached a high level.

[0216] Thermal stability optimization

[0217] The thermal decomposition temperature of each example exceeded 300°C, and Example 4 reached 320°C, which proves that the introduction of nano-enhancers and cross-linked structures effectively improves the structural stability of the lubricating oil at high temperatures and reduces the risk of thermal decomposition of the oil. This thermal stability is crucial in high-temperature applications of enameled wire.

[0218] Excellent antioxidant properties

[0219] The oxidation induction time (OIT) of the lubricating oil of the present invention in the anti-oxidation test is significantly prolonged, reaching up to 47 minutes (Example 4), indicating the high efficiency of the antioxidant in the lubricating oil system of the present invention. The addition of the antioxidant can effectively prevent oxidative degradation in a high temperature environment, maintain the long-term stability of the lubricating oil, and provide a guarantee for the service life of the lubricating oil in a high temperature environment.

[0220] Excellent UV stability

[0221] The test results of the UV absorbance decay rate show that the absorbance of all examples after UV irradiation decreased by less than 10%, among which Example 4 had the lowest decay rate of only 6%, demonstrating the excellent stability of the lubricant in a light aging environment. This performance is due to the effective effect of the UV stabilizer, which helps to improve the application stability of the lubricant in an environment that may be exposed to outdoor or UV rays.

[0222] Excellent adhesion and lubricity

[0223] The adhesion level of each example reached level 0-1 (level 0 is the best), and the friction coefficient test was kept within the range of 0.09-0.12. In particular, Example 4 performed outstandingly, reaching the lowest friction coefficient of 0.09 and the best adhesion level of 0. This result verifies that the present invention significantly improves the surface adhesion and lubrication performance of the lubricating oil through the synergistic effect of the nitrogen-containing monomer with a nitrogen heterocyclic structure and the polyether-modified silicone oil, ensuring the lubrication and long-term protection performance of the enameled wire.

[0224] In general, the present invention achieves comprehensive performance improvement of high flame retardancy, excellent thermal stability, antioxidant property and adhesion by optimizing the selection of base oil, the synergistic ratio of phosphorus-containing and nitrogen-containing monomers, the organic modification of nano-enhancers and the reasonable addition of antioxidants and ultraviolet light stabilizers.

[0225] Comparative experiment 1: Flame retardancy comparison experiment

[0226] Objective: To evaluate the flame retardant properties of the lubricating oil of the present invention, specifically including the thickness of the carbonized layer and the burning time, in order to demonstrate the synergistic flame retardant effect of the phosphorus-containing monomer and the nitrogen-containing monomer.

[0227] The experimental groups set up in this comparative experiment are as follows:

[0228] Comparative Example 1: No phosphorus-containing monomer

[0229] The only difference from Example 1 is that no phosphorus-containing monomer is added, the proportions of other components remain unchanged, the balance is supplemented with base oil, and the preparation steps remain unchanged.

[0230] Comparative Example 2: No nitrogen-containing monomer

[0231] The only difference from Example 1 is that no nitrogen-containing monomer is added, the proportions of other components remain unchanged, the balance is supplemented with base oil, and the preparation steps remain unchanged.

[0232] Comparative Example 3: No flame retardant ingredients

[0233] The only difference from Example 1 is that no phosphorus-containing monomer and nitrogen-containing monomer are added, the proportions of other components remain unchanged, the balance is supplemented with base oil, and the preparation steps remain unchanged.

[0234] The experimental steps are as follows:

[0235] 1. Coating and drying: The lubricating oil examples and comparative examples are uniformly coated on the surface of the enameled wire and left to dry until the oil film is stable;

[0236] 2. Heating flame retardant test:

[0237] Place the sample into the flame retardant tester and gradually heat it to 450°C;

[0238] The burning time (seconds) and the thickness of the char layer formed (micrometers) were recorded for each sample.

[0239] The experimental results are shown in the following table:

[0240] .

[0241] From the above flame retardancy comparison experiment, it can be obtained that:

[0242] 1. Significant effect of synergistic flame retardant mechanism

[0243] The combustion time of the embodiment of the present invention is 65 seconds, and the thickness of the carbonized layer is 20 microns, which is significantly better than the comparative example. This shows that the combination of phosphorus-containing and nitrogen-containing monomers has a high degree of synergy in flame retardancy;

[0244] Phosphorus-containing monomers decompose under high temperature conditions to generate phosphoric acid compounds, which quickly form a dense carbonized layer on the sample surface, effectively isolating oxygen and heat sources and acting as a physical barrier.

[0245] The nitrogen-containing monomer releases inert gas at high temperature, diluting the oxygen in the combustion zone and further inhibiting the spread of flames. The combination of the two achieves the rapid formation of the carbonized layer and the stable gas phase flame retardant effect. This innovative synergistic flame retardant mechanism ensures that the flame retardancy of the lubricant of the present invention is greatly improved in high temperature environments.

[0246] 2. The flame retardant performance of the comparative example is significantly reduced

[0247] In Comparative Example 1, the sample lacking the phosphorus-containing monomer showed a significant decrease in flame retardancy, with the burning time shortened to 35 seconds and the thickness of the carbonized layer reduced to 10 microns. Due to the lack of the carbonization effect of the phosphate group, the ability to form a flame retardant protective layer is insufficient, and the flame retardant effect is greatly reduced;

[0248] Comparative Example 2 lacks nitrogen-containing monomers, and its combustion time is shortened to 40 seconds, and the thickness of the carbonized layer is 12 microns. Although the carbonized layer still exists, it lacks the inert gas released by the nitrogen group, and cannot achieve effective gas phase flame retardancy, and the flame retardancy is obviously inferior to that of the embodiment of the present invention;

[0249] In Comparative Example 3, which lacks both phosphorus-containing monomers and nitrogen-containing monomers, the burning time is only 20 seconds, the thickness of the carbonized layer is only 5 microns, and there is almost no flame retardant effect. This result shows that the flame retardant mechanism of phosphorus-containing and nitrogen-containing monomers plays a core role in the flame retardant performance of the lubricating oil of the present invention;

[0250] In general, the combination of the carbonization effect of the phosphorus-containing monomer and the gas phase flame retardant effect of the nitrogen-containing monomer provides dual flame retardant protection for the lubricant of the present invention, ensuring the reliability and safety of the enameled wire under high temperature conditions. The phosphorus-containing and nitrogen-containing monomers form a multi-level flame retardant protection system through the interaction of physical barriers and inert gases, which significantly improves the flame retardant efficiency and durability of the lubricant.

[0251] Comparative experiment 2: Thermal stability comparison experiment

[0252] Purpose: To evaluate the thermal stability of the lubricating oil of the present invention.

[0253] The experimental groups set up in this comparative experiment are as follows:

[0254] Comparative Example 4: No Nano-Enhancement Agent

[0255] The only difference from Example 1 is that no nano-enhancer is added, the proportions of other components remain unchanged, the balance is supplemented with base oil, and the preparation steps remain unchanged.

[0256] Comparative Example 5: Unmodified Nanoenhancer

[0257] The only difference from Example 1 is that the nano-enhancing agent is unmodified montmorillonite nanosheets.

[0258] The experimental steps are as follows:

[0259] 1. Sample preparation: Prepare samples according to the embodiment scheme and the comparative example scheme;

[0260] 2. Thermal stability test:

[0261] A thermogravimetric analyzer (TGA) was used to heat the sample from room temperature to 600 °C at a heating rate of 10 °C / min.

[0262] The initial decomposition temperature (the temperature at which the mass loss reaches 5%) and the total mass loss percentage at 500 °C were recorded for each sample.

[0263] The experimental results are shown in the following table:

[0264] .

[0265] From the above thermal stability comparison experiment, we can get:

[0266] 1. Significant thermal stability of organic modified nanoenhancers

[0267] Example 1 exhibits excellent thermal stability in terms of initial decomposition temperature and mass loss at high temperature. The initial decomposition temperature reaches 320°C, and the mass loss rate at 500°C is 18%, which is significantly better than the two comparative examples. The experimental results show that the addition of organically modified montmorillonite nanosheets forms a strong physical barrier that can effectively block the rapid transfer of heat and the escape of decomposition products, thereby significantly improving the stability of lubricants in high temperature environments. This physical barrier effect verifies the core role of the innovative design of nano-enhancers in improving thermal stability;

[0268] 2. The thermal stability of the control group without nano-enhancement agent is significantly reduced

[0269] In Comparative Example 4 (without nano-enhancer), the initial decomposition temperature of the sample was reduced to 285°C, and the mass loss rate was as high as 32% at 500°C. The absence of nano-enhancer directly led to the accelerated thermal decomposition of the lubricating oil, proving the key role of nano-enhancer in providing thermal stability protection under high temperature environment. This result emphasizes the importance of nano-enhancer in the design of the present invention, indicating that the addition of nano-enhancer significantly improves the stability of the lubricating oil under extreme environment;

[0270] 3. Importance of organic functional group modification

[0271] Although the initial decomposition temperature of Comparative Example 5 (unmodified montmorillonite nanosheets) is increased (300°C), the thermal stability is still not as good as that of Example 1, and the mass loss rate is 25% at 500°C. This shows that the unmodified nanosheets have poor dispersibility in lubricating oils, insufficient interfacial bonding force, and cannot form a stable physical barrier in the molecular structure. The organically modified montmorillonite nanosheets used in the present invention, due to their surface functional group modification, form better molecular bonding with the base oil and flame retardant components, thereby achieving more efficient thermal stability. This design highlights the innovation and practicality of the nano-enhancer in the lubricating oil system of the present invention.

[0272] The present invention significantly improves the thermal stability of lubricating oil by introducing montmorillonite nanosheets modified with organic functional groups, verifying the unique synergistic effect of nano-enhancers. Experimental data show that organically modified nanosheets can effectively delay the thermal decomposition process in a high temperature environment and enhance the thermal stability of lubricating oil, which is better than the unmodified or unadded comparative sample.

[0273] Comparative experiment 3: Adhesion comparison experiment

[0274] Objective: To evaluate the adhesion of the lubricant of the present invention on the surface of enameled round aluminum wire.

[0275] The experimental groups set up in this comparative experiment are as follows:

[0276] Comparative Example 6: No nitrogen-containing monomer

[0277] The only difference from Example 1 is that no phosphorus-containing monomer is added, the proportions of other components remain unchanged, the balance is supplemented with base oil, and the preparation steps remain unchanged.

[0278] Comparative Example 7: Nitrogen-containing monomer without polar groups

[0279] The only difference from Example 1 is that the nitrogen-containing monomer is a nitrogen-containing monomer without a polar group.

[0280] The experimental steps are as follows:

[0281] 1. Sample preparation: Prepare each sample according to the embodiments and comparative examples of the present invention;

[0282] 2. Adhesion test:

[0283] Each lubricating oil sample is evenly coated on the surface of the enameled wire and dried;

[0284] Use the cross-hatch test method to draw a grid with a spacing of 1 mm on the coating surface;

[0285] Use tape to pull on the mesh surface and observe the peeling of the coating;

[0286] Record the adhesion rating of the coating (0-5, with 0 being the best).

[0287] The experimental results are shown in the following table:

[0288] .

[0289] From the above adhesion comparison experiment, we can get:

[0290] 1. The polar groups of nitrogen-containing monomers enhance adhesion

[0291] The adhesion level of Example 1 is 0, and there is no peeling phenomenon, which shows that the nitrogen heterocyclic structure containing polar pyrrolidone groups significantly improves the adhesion of the lubricant on the surface of the enameled wire. The polar group forms a good interaction force with the surface of the enameled wire, enhances the surface adhesion of the lubricant, and prevents the coating from falling off;

[0292] 2. The comparative example without nitrogen-containing monomers significantly reduced adhesion

[0293] The adhesion level of comparative example 6 is 3, and partial peeling occurs, indicating that the lack of polar interaction force of nitrogen-containing monomers leads to reduced adhesion of the lubricant coating on the surface of the enameled wire. This result proves the key role of nitrogen-containing monomers in improving the adhesion of lubricants;

[0294] 3. Nitrogen-containing monomers without polar groups show poor adhesion

[0295] The adhesion level of Comparative Example 7 is 2, and the adhesion is slightly improved, but the effect is not as good as that of Example 1. This shows that the presence of polar groups helps to enhance the surface binding force of lubricating oil, while the simple nitrogen monomer lacks sufficient polar interaction, resulting in insufficient adhesion and easy to produce a small amount of peeling phenomenon.

[0296] The present invention significantly improves the adhesion of lubricating oil on the surface of enameled wire by introducing polar groups in nitrogen-containing monomers. Experimental results show that nitrogen-containing monomers containing polar groups improve the adhesion of lubricating oil through intermolecular interaction forces, thereby avoiding coating peeling.

[0297] Comparative experiment 4: Friction coefficient comparison experiment

[0298] Objective: To evaluate the lubricating performance of the lubricating oil of the present invention on the surface of enameled round aluminum wire, and the specific test content is the friction coefficient.

[0299] The experimental groups set up in this comparative experiment are as follows:

[0300] Comparative Example 8: No polyether modified silicone oil

[0301] The only difference from Example 1 is that: instead of using polyether-modified silicone oil, unmodified silicone oil is used as the base oil, and the proportions of other components and the preparation steps remain unchanged.

[0302] Comparative Example 9: Using traditional base oil

[0303] The only difference from Example 1 is that conventional mineral oil is used instead of polyether-modified silicone oil, and the proportions of other components and the preparation steps remain unchanged.

[0304] The experimental steps are as follows:

[0305] 1. Sample preparation: Prepare each sample according to the embodiments and comparative examples of the present invention;

[0306] 2. Friction coefficient test:

[0307] Use a friction tester, set the sliding speed to 10 mm / s, and apply a load of 5 N;

[0308] Apply the lubricant sample evenly on the friction surface and slide it for 30 minutes under the test conditions;

[0309] The coefficient of friction (unitless) was recorded for each sample.

[0310] The experimental results are shown in the following table:

[0311] .

[0312] From the above friction coefficient comparison experiment, we can get:

[0313] 1. Polyether modified silicone oil significantly reduces the friction coefficient

[0314] The friction coefficient of Example 1 of the present invention is 0.10, which is significantly lower than that of the comparative sample. The polyether-modified silicone oil as a base oil not only has low friction characteristics, but also its silicon-oxygen chain structure gives it extremely low surface tension, ensuring the formation of an efficient lubricating layer in sliding contact, reducing friction and wear, and is suitable for high-speed and high-temperature environments;

[0315] 2. The lubricity of unmodified silicone oil is poor

[0316] In Comparative Example 8 (unmodified silicone oil), the friction coefficient is 0.15, which is significantly higher than that of Example 1 of the present invention. The unmodified silicone oil lacks the lubrication enhancement effect of the polyether group, and the adhesion and stability of the lubricating layer are insufficient, resulting in an increase in the friction coefficient, and the lubricity is inferior to that of the polyether-modified silicone oil;

[0317] 3. Conventional mineral oil exhibits the highest friction coefficient

[0318] The friction coefficient of comparative example 9 (mineral oil base oil) is 0.18, showing poor lubrication performance. This is because mineral oil is prone to failure under high temperature and high load conditions and it is difficult to form a stable lubrication layer. In contrast, the lubricating oil of the present invention achieves a significant reduction in friction coefficient by adding polyether-modified silicone oil, ensuring the long-term lubrication performance of the lubricating oil in a high temperature and high speed environment.

[0319] The invention significantly improves the lubricating performance of lubricating oil by introducing polyether-modified silicone oil, so that it has a lower friction coefficient and a highly efficient lubricating effect, which verifies the key role of base oil selection in the invention. Experimental data show that polyether-modified silicone oil has significant lubrication advantages over unmodified silicone oil and traditional mineral oil.

[0320] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. Flame retardant cable lubricant suitable for enameled round aluminum wire, characterized by: The composition comprises the following components by weight percentage: 40-60 wt% of base oil, 10-30 wt% of phosphorus-containing monomer, 10-20 wt% of nitrogen-containing monomer, 1-5 wt% of initiator, 1-5 wt% of cross-linking agent, 3-8 wt% of nano-enhancer and 0.1-1 wt% of functional additive; The base oil is a polyether-modified silicone oil formed by alternating copolymerization of polyether groups and siloxane segments, and its molecular structure contains multiple ether bonds and siloxane bonds; The phosphorus-containing monomer is a comonomer having a phosphate functional group, the structure of which contains at least one phosphorus-oxygen bond and can form a covalent bond with the base oil segment during the polymerization process; The nitrogen-containing monomer is a polar monomer having a nitrogen heterocyclic structure, and its molecular structure contains a pyrrolidone group, which can form a copolymer with the base oil and the phosphorus-containing monomer in the polymerization reaction; The nano-enhancer is a montmorillonite nanosheet with a surface modified by an organic functional group; The crosslinking agent is trimethylolpropane triacrylate.

2. The flame-retardant cable lubricant suitable for enameled round aluminum wire according to claim 1, characterized in that: The functional additives include: Antioxidants, accounting for 0.3-1wt% of the total mass of the lubricant; UV stabilizer, accounting for 0.1-0.5wt% of the total mass of the lubricant.

3. A method for preparing a flame-retardant wiring lubricant suitable for enameled round aluminum wire according to claim 1 or 2, characterized in that: The following steps are involved: S1. Heat the base oil to 40-60°C and degas under vacuum for 10-30 minutes; S2. Add the phosphorus-containing monomer to the base oil, control the stirring speed at 100-200 rpm, and stir for 10-30 minutes; S3. Slowly add the nitrogen-containing monomer into the base oil, control the stirring speed at 100-200 rpm, and stir evenly; S4, add initiator and crosslinking agent at 70-110°C and keep stirring for 2-5 hours; S5, cooling the reaction system to room temperature, continuing stirring for 30-60 minutes, and degassing for 10-20 minutes; S6. Add base oil to adjust the viscosity to 150-200 cSt.

4. The preparation method according to claim 3, characterized in that: Before the step S4, the method further includes: dispersing the nano additive and a small amount of base oil by ultrasonic for 20-40 minutes, and then adding the nano additive into the base oil and stirring evenly.

5. The preparation method according to claim 3, characterized in that: Before the step S6, the method further includes: adding an antioxidant and an ultraviolet light stabilizer when the temperature of the reaction system is 30-50° C., and stirring evenly.

6. A method for applying the flame-retardant wiring lubricant oil suitable for enameled round aluminum wire according to claim 1 or 2, characterized in that: The method comprises the following steps: applying lubricating oil evenly on the surface of the enameled wire to ensure that the lubricating oil is fully covered.

Citation Information

Patent Citations

  • Lubricating oil composition and preparation method thereof

    CN106147953A

  • High-temperature-resistant polytetrafluoroethylene lubricating grease for sealing and preparation method thereof

    CN109135872A